Knowledge, attitude and practices about hepatitis B in paramedical and supporting staff at a tertiary care hospital: a cross sectional study - Nimbvikar, Apoorv A.; Gandhi, Janhavi S. (International Journal Of Community Medicine And Public Health, 2022)
Background: Healthcare workers including nurses, lab technicians and multi-purpose workers are at a higher risk of contracting hepatitis B virus infection than the general population as they are exposed to blood, body fluids and sharps due to their professional activities. The objective of this study was to compare the knowledge about hepatitis B infection, its transmission and prevention among two groups, nurses and lab technicians versus MPWs. Methods: A cross-sectional study was carried out among 257 nurses and lab technicians versus 159 MPWs working at a tertiary care center. After clearance by the institutional ethical committee and informed consent of the participants, they were requested to fill a close ended questionnaire. The data was analyzed statistically using the JASP software. Results: The self-perceived risk of contracting infectious diseases owing to their profession was similar in nurses and lab technicians and MPWs. The awareness about hepatitis B infection, all the correct modes of transmission of the virus and the chances of the infection leading to liver diseases and cancer was higher in nurses and lab technicians than in MPWs. Awareness regarding prevention of infection and the vaccination rates were also higher among nurses and lab technicians. Knowledge about methods of prevention of the infection was found to be significantly more among the nurses and lab technicians. Conclusions: Overall, there is a significant gap in the knowledge about hepatitis B infection, its transmission and prevention in the MPWs. Vaccination coverage is also low in MPWs.